STATEMENT OF THE AMERICAN ASSOCIATION FOR RESPIRATORY CARE TO THE SUBCOMMITTEE ON AVIATION COMMITTEE ON PUBLIC WORKS AND TRANSPORTATION UNITED STATESHOUSE OF REPRESENTATIVES (Tufts Archival Research Center, 2007)
Statement of the American Association for Respiratory Care for the House Aviation Subcommittee on legislation to ban smoking aboard aircraft in October of 1987. Emphasizes need to ban smoking on all domestic flights in the United States. Maintains that ventilations systems are not adequate to filter air that has been mixed with cigarette smoke.